Mídia social para a indústria criativa: reflexões sobre possíveis contribuições da Dicipa para a comunicação científica da Unipampa - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The aim of the present work is to reflect upon the possible contributions of the Scientific Dissemination of Pampa (Dicipa) multi-platform strategies – communicational action of our own design, as a result of a Research, Development and Innovation project (PD&I) –, made for the Federal University of Pampa (Unipampa). Conceiving the Dicipa multiplatform strategies as social media for creative industry, the main goal of this thesis is to present the possible contributions of the scientific-theoretical, scientific-practical and social fields of the above-mentioned communicational action to Unipampa’s scientific communication. To this end, this work expatiates on creative industry and university, in order to connect the two expressions and to present the university as a creative industry (Chapter 2), and on the concepts guiding its reflection: cyberculture, culture of convergence, social media and scientific communication (Chapter 3); it also presents the planning and carrying out of the multi-platform strategies of Scientific Dissemination of Pampa (Chapter 4); and, finally, it discusses the possible contributions of this action – Dicipa – to Unipampa’s scientific communication (Chapter 5). This research is justified in the scientific-theoretical field as it provides reflection upon the research and development as resources for creative industry and, therefore, allowing our argumentation conceiving Unipampa as a creative industry; it is also justified in the scientific-practical field in what concerns the reflection of the use of social media (communicational action) in the scientific context and, at the same time, in the organizational context of the universities, i.e., when it shows that it is possible to develop actions aiming to contribute to the scientific communication with the aid of physical, human and intellectual resources, previously available at the institution; and, finally, in the social field, promoting a debate on the importance of scientific dissemination – one of the branches of scientific communication – to society, and on people’s readiness to take part in the decisions concerning Science, Technology and Innovation (STI). Amongst the identified contributions, this work highlights the visibility brought to research groups and graduate programs; the democratization of scientific information; the communicative horizontality and bidirectionality; the possibility of discussion among peers and teamwork and the contact of society with scientific issues.
Keywords: Mídia social; Comunicação na ciência; Política cultural; Computadores e civilização; Universidade Federal do Pampa; Social media; Communication in Science; CNPQ::CIENCIAS SOCIAIS APLICADAS